Near/Middle East: Round-up of Friday sermons 16 Jan 04 (BBC Monitoring Middle East, 2004)
"O Muslims," the imam continues, "if you pray to God in good faith, seek his reward, abandon sins, and fear his punishment, then you have achieved real piety in your practical life. And, through life, you shall fulfil your duty to your Creator and brethren in religion. All manifestations of pilgrimage, O God's subjects, lead to this very aim. All Muslims are like one body. They are like the bricks of a wall supporting each other. In the blessed pilgrimage sites, Muslims experience moments that embody the meanings of piety and produce the strong feeling of brotherhood that unifies Muslims, irrespective of their colour and tongue. When the pilgrims replace their normal dress with the uniform pilgrimage attire, they become the same. They face the same God with the same prayer." Concluding his sermon, Shaykh [Ahmad Turuk] prayed to God: "O Lord, forgive our guilts, support us and grant us victory over the infidels. O Lord, forgive all our guilts, relieve all our worries, allow us to pay all our debts, heal all our sick, guide all Muslims who are disobedient, support all victims of injustice and stand against all unjust people. We ask you with your 99 attributes, with your superior qualities and with your greatest name to support our Muslim brothers in Palestine, support Muslims in Iraq and support all Muslims everywhere. O Lord, we complain to you from our weakness, from our ability and from being humiliated by others. You are the god of the weak and you are the god of Muslims. We resort to you to avoid your wrath. O Lord, destroy anyone that has evil intentions against us, against Muslims' countries or against the holy places of Muslims. O Lord, support Islam and strengthen Muslims. O Lord, support Islam and strengthen Muslims [as heard]." The sermon ended at 1026 gmt with duration of 16 minutes. At 1000 gmt Egyptian radio began a live relay of Friday prayers from the mosque of martyr Awni in Ayn Shams district in Cairo; the sermon, which began at 1010 gmt and lasted 21 minutes, was delivered by professor Muhammad Sayyid Al-Musayyar, the professor at Al-Azhar university, and its main theme was the prerequisites of the Muslim pilgrimage journey. The total length of the prayer proceedings was 37 minutes. The preacher began the sermon by praising God Almighty and prophet Muhammad and spoke about the importance of performing pilgrimage properly in order to gain the hoped for rewards; the preacher cited the three pillars which must be present prior to and following the pilgrimage journey, namely sincere repentance for past sins, funds earned legitimately, good manners and sound thinking. The preacher added: "We need mental awareness, sound reasoning and mature thinking and to emulate the manners of prophet Muhammad"; he wrapped up the first part of the sermon by calling on all to care for their parents, particularly if they are elderly, and improve on their manners, especially in not harming one's neighbors. In the second part of the sermon, the preacher called on all to be virtuous and to obey God Almighty. In the concluding prayers, the preacher said: "O God Almighty, make us fear Thou to avoid falling into disobedience, make our faith in [your worship] so firm as to withstand the trials of life, make us enjoy our hearing, vision and strength, make us avenge ourselves from those who have been unjust to us, make us victorious over our enemies, do not put our faith to the test and do not make life on earth what we strive for the most, do not subject us to those who do not have fear Thou or have mercy on us, guide Muslim leaders to achieve the benefit and prosperity of all, back Muslims to achieve victory and grant our nation security, prosperity and peace.